2015
DOI: 10.1111/jep.12307
|View full text |Cite
|
Sign up to set email alerts
|

Which risk‐adjustment index performs better in predicting 30‐day mortality? A systematic review and meta‐analysis

Abstract: Although all the selected risk-adjustment indices perform equally well, SAPS seems better than other indices for short-term mortality based on scaled ranking score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…Based on "PubMed" database search using terms "in-hospital mortality," "in-hospital deaths," and "inter-hospital transfers" and after review of other mortality prediction models, we identified 30 putative variables (see Table 1) for inclusion in the mortality model. 5,14,15,18,26 Demographic data included age and gender. Admit type was defined as an emergency, urgent, and routine.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on "PubMed" database search using terms "in-hospital mortality," "in-hospital deaths," and "inter-hospital transfers" and after review of other mortality prediction models, we identified 30 putative variables (see Table 1) for inclusion in the mortality model. 5,14,15,18,26 Demographic data included age and gender. Admit type was defined as an emergency, urgent, and routine.…”
Section: Variablesmentioning
confidence: 99%
“…4,11,12 Recognizing these complexities clinicians have expressed an interest in adopting evidencebased clinical prediction models to increase their prognostic confidence in the end-of-life care. 13 Available models predicting mortality are often limited to ICU settings, 14 are condition-specific, [15][16][17][18] or predict deaths after hospital discharge. [19][20][21] Multiple early warning systems (EWS) have been developed that use vital sign abnormalities prior to clinical deterioration with efforts to predict in-hospital mortality, but these models are limited by poor sensitivity, poor positive predictive value, and low reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite a great amount of evidence on short-term prognosis is available, only a few studies investigated the predictors of mortality beyond the first 30 days after acute PE [ 8 , 9 , 10 ], and in the elderly the prognostic value of clinical prediction rules and comorbidities burden has not been clearly established. The use of the sPESI score as may be interesting due to its simplicity and widespread use, and comorbidities may have a significant impact on long-term mortality [ 11 , 12 ], especially in elderly subjects who are likely to have a higher comorbidity burden [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A uniform limitation of many administrative database analyses is the lack of patient-level severity of illness scoring. However, comorbidity-based risk-adjustment indices (e.g., Charlson index AUROC = 0.67) have been shown to perform similarly well as severity of illness scores (APACHE II AUROC = 0.805 and SAPS II AUROC = 0.843) in predicting short-term mortality following ICU admission [18][19][20]. The discriminative ability of our comorbidity-based mortality model, while still dependent on ICD-9-CM-based coding instead of physiologic variables, compares favorably (AUROC = 0.80).…”
Section: Discussionmentioning
confidence: 99%